Postacute Sequelae of SARS-CoV-2 in University Setting - Megan Landry; Sydney Bornstein; Nitasha Nagaraj; Gary A. Sardon; Amanda Castel; Amita Vyas; Karen McDonnell; Mira Agneshwar; Alyson Wilkinson; Lynn Goldman (Emerging Infectious Diseases, 2023)
Postacute sequelae of SARS-CoV-2 infection, commonly known as long COVID, is estimated to affect 10% to 80% of COVID-19 survivors. We examined the prevalence and predictors of long COVID from a sample of 1,338 COVID-19 cases among university members in Washington, DC, USA, during July 2021‒March 2022. Cases were followed up after 30 days of the initial positive result with confidential electronic surveys including questions about long COVID. The prevalence of long COVID was 36%. Long COVID was more prevalent among those who had underlying conditions, who were not fully vaccinated, who were female, who were former/current smokers, who experienced acute COVID-19 symptoms, who reported higher symptom counts, who sought medical care, or who received antibody treatment. Understanding long COVID among university members is imperative to support persons who have ongoing symptoms and to strengthen existing services or make referrals to other services, such as mental health, exercise programs, or long-term health studies.